Aristotelian Concept of Happiness (Eudaimonia) and its Conative Role in Human Existence: A Critical Evaluation - Egbekpalu, Purissima Emelda (Conatus - Journal of Philosophy, 2021)
Despite the challenges of human existence, identifying the major features that sustain man’s striving to persist in life (conatus) is very essential in understanding who man is. This paper critically evaluates Aristotelian concept of happiness (eudaimonia) and its conative role in human existence as it ignites newness of interest in Aristotelian theory of happiness as the ultimate end of all human activities. Aristotle’s notion of happiness connotes conative experiences; actions that signify movements of some sorts for preservation of life. With regard to self-preservation in existence, Aristotle held the opinion that man has the natural inclination to actualize his potentialities through strong efforts of the will towards the right, and at the same time to create new potentialities to sustain his life. Through the activities of the soul (virtuous acts), man propels himself in a distinctive way towards objects of his desire for survival and flourishing. His concept of emotions as having the affective, cognitive as well as behavioural dimensions revealed that emotions have psychological values and vital functions which serve as survival instinct in man. However, they differ in their aims in that they have both attractive and aversive characteristics such that they move him either to seek or to avoid necessary objects that enhance or harm his existence, respectively. Considering the subjective experiences of pains and pleasures of emotions, they dispose man to virtuous actions towards excellence. However, to sustain man’s inner drive to persist in life, this paper objects to the theses that happiness can be restricted to only cognitive activities. Despite the weaknesses of his treatise concerning happiness in relation to man’s striving to persist, it was observed that Aristotle’s notion of happiness aids man’s striving in life. For further studies, it recommended clarification of ambiguous concepts and reconciliation of contradictions inherent in the theory.